Using Mobile Technology for Fostering Intellectual Engagement - Preciado Babb, Armando Paulino; Saar, Candace; Marcotte, Chenoa; Brandon, Jim; Friesen, Sharon (International Journal of Interactive Mobile Technologies (iJIM), 2013)
Student engagement, and in particular intellectual engagement, has been identified as a key factor in learning at the high school level. While this type of engagement has an impact on student learning in fields related to science, technology, engineering and mathematics (STEM), it also has a positive impact on the learning of other disciplines such as English, Fine Arts, and Social Sciences. This report describes a set of projects co-designed by teachers and education specialists aimed at engaging students intellectually in each major high school subject area. Student use of mobile technologies, in this case the iPad2, features prominently in each of these projects. Interviews with teachers and students were conducted in order to identify evidence of intellectual engagement, as well as studentsâ?? interactions with the mobile device. Data from a survey was also used to identify the level of engagement of students involved in these projects.